The Influence of Ethics and Organizational Culture on the Work Environment on Employees State Civil Apparatus Sub-District Office Karawaci in Tangerang - Akbar Maulana Pujangga (PT Publikasiku Academic Solution, 2023)
This study aims to determine and analyze the influence of ethics, organizational culture on the work environment on civil servants of the State Office of Karawaci District Office in Tangerang. In this study, the sample used was 60 employees of the State Civil Apparatus at the Karawaci District Office in Tangerang. Data collection is carried out through direct observation and library research obtained through interviews and internal organization data collection and relevant references. This study uses a model of validity analysis, reliability analysis, analysis of the coefficient of determination, and correlation analysis. From the results obtained by the influence of ethics and organizational culture on the work environment as evidenced by a positive relationship aimed at calculating the probability value obtained at a significant level of 0.000 because 0.000 <0.005, then it can be ascertained for ethical variables (X1) and organizational culture (X2) together affect the work environment variable (Y). While the analysis of the coefficient of determination (KD) is produced from the value of Adjusted R Square of 0.857. This shows that as much as 85.7% of ethics and organizational culture simultaneously affect the work environment and the remaining 14.3% affect other factors not examined in this study.